Cornea donors who have had prior refractive surgery: data from the Eye Bank Association of America. Issue 4 (July 2016) - Fargione, Robert A.; Channa, Prabjot
Abstract : Purpose of review: Millions of Americans have undergone refractive surgeries, including radial keratotomy, photorefractive keratectomy, and laser-assisted in situ keratomileusis. Eye Bank Association of America medical standards do not permit corneas from patients who have undergone refractive procedures to be used in penetrating keratoplasty, anterior lamellar keratoplasty, or tectonic grafting procedures. Such corneas, can, however, be used for endothelial corneal transplantation. The objective of this article is to provide an update on current trends for the screening and usage of corneas that have undergone refractive surgery. Recent findings: Several case reports have highlighted the difficulty in using postrefractive surgery corneas in penetrating keratoplasty. However, tissue with anterior stromal flaws, including a history of refractive surgery, has been used in endothelial keratoplasty with equivalent outcomes in topography, endothelial cell count, and visual acuity. Many modalities for proper identification of postmortem donor corneas that have undergone refractive surgery have been studied. Summary: Corneas with a history of refractive surgery have found use in endothelial keratoplasty. Multiple objective methods of tissue identification have been investigated to avoid the use of these corneas in penetrating or anterior keratoplasty surgeries.